2020
DOI: 10.1186/s12885-020-07639-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postmastectomy radiotherapy in node-positive triple-negative breast cancer

Abstract: Background The value of postmastectomy radiotherapy (PMRT) for pathological node-positive triple-negative breast cancers (TNBC) remains debatable. The aim of this population-based retrospective study was to evaluate the effect of PMRT on survival outcomes in this population. Methods Patients diagnosed with stage T1-4N1-N3M0 TNBC between 2010 and 2014 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. We used univariate and multivariate Cox regression hazards method to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Accordingly, we not only divided the subgroup analysis according to the clinicopathological characteristics but also performed subgroup analysis by crossing tumor size with the number of positive LNs, which proved that only BCSS in T2 patients with three positive LNs could benefit from PMRT. Zhang et al studied the effect of PMRT on the survival of T1-4N1-N3M0 patients, and the results showed that there was no difference in BCSS between PMRT and non-PMRT cohort in the T1-2N1 subgroup (P = 0.191) [24], which was consistent with our results, but they did not conduct further stratified analysis. Another study included 675 T1-2N1M0 TNBC patients and subgroup analysis was performed based on the number of positive lymph nodes.…”
Section: Plos Onesupporting
confidence: 87%
“…Accordingly, we not only divided the subgroup analysis according to the clinicopathological characteristics but also performed subgroup analysis by crossing tumor size with the number of positive LNs, which proved that only BCSS in T2 patients with three positive LNs could benefit from PMRT. Zhang et al studied the effect of PMRT on the survival of T1-4N1-N3M0 patients, and the results showed that there was no difference in BCSS between PMRT and non-PMRT cohort in the T1-2N1 subgroup (P = 0.191) [24], which was consistent with our results, but they did not conduct further stratified analysis. Another study included 675 T1-2N1M0 TNBC patients and subgroup analysis was performed based on the number of positive lymph nodes.…”
Section: Plos Onesupporting
confidence: 87%
“…Tumor size and number of axillary lymph node metastases have been proved to be closely related to recurrence and prognosis of breast cancer [20,21].In our study, tumor size and number of positive LNs were associated with BCSS.The effect of PMRT mainly depends on the comprehensive consideration of tumor size and the number of positive LNs [22], and secondly, it is related to other high-risk factors such as young age and positive vascular tumor thrombus.Accordingly, we not only divided the subgroup analysis according to the clinicopathological characteristics, but also performed subgroup analysis by crossed tumor size with number of positive LNs, which proved that only BCSS in T2 patients with three positive LNs could bene t from PMRT.Zhang et al studied the effect of PMRT on the survival of T1-4N1-N3M0 patients, and the results showed that there was no difference in BCSS between PMRT and non-PMRT cohort in the T1-2N1 subgroup (P = 0.191) [23], which was consistent with our results, but they did not conduct further strati ed analysis.Another study included 675 T1-2N1M0 TNBC patients and subgroup analysis was performed based on the number of positive lymph nodes. After a median followup of 37 months, PMRT was independently associated with increased OS, but there was no improvement in BCSS in any subgroup [24].The reason why they are inconsistent with our conclusion may be due to their shorter follow-up time and fewer cases.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no more details of this case were reported [168]. A separate study regarding patients with TNBC, performed post-mastectomy RT and reported a beneficial impact on 3-year breast cancer-specific survival which was dependent on the pathological stage of the patients [169].…”
Section: Breast Cancermentioning
confidence: 95%